IDENTITAS NASIONAL SEBAGAI KARAKTER BANGSA AKTUALISASI PEMBERDAYAANNYA MELALUI REVITALISASI PANCASILA - Siswomihardjo, Koento Wibisono (PKn Progresif, 2008)
Reform in 1998 has changed the view of the world to Indonesia. At the time Indonesia was known as a country that has the resilience and a solid integration of the nation. However, it views these claims only studios. Because the nation's unity and unity is built with an iron hand and a threat to anyone who make criticisms to the country. But the characters to form the Indonesian nation must be a better nation that is based on the ideology of Pancasila. Thus, to answer confusion and problematic condition of the nation which Indonesia is the time to make the revitalization of Pancasila.